3D analysis of dental arch area and occlusal index of children with cleft lip and palate at 5 years of age - Cantos, Grace Alejandra Cabezas (2020)
Objective: The aim of this study was to compare the dental arch area and occlusion of children with cleft lip and complete unilateral palate at 5 years using the Atack occlusal index. Material and Methods: The sample consisted of 124 digital models of children with cleft lip and unilateral palate. The measurement of the area of the dental arches was obtained by Stereophotogrammetry System Software. Atack occlusal index analyzed the occlusion on digitized dental models. The Interclass Correlation Coefficient was used to analyze the intra-examiner reproducibility and the Spearman correlation coefficient verified the correlation between the dental arch area and occlusal index. Results: For intra-examiner agreement analysis, measurements of the 1st and 2nd measurements of half of the sample were obtained 15 days after the first measurement. The ICC showed high agreement (0.83). The Atack occlusal index presented with a prevalence of index 4 (34.64%). Regarding the measurements of area (cm2), the median value was 7.28, minimum value 4.90 and a maximum 11.89. The correlation between the dental arch area and occlusal index was negative (-0.35). Conclusion: The occlusal index has no correlation with the area, which means that the palate area is not a determinant in the Atack occlusal index